2016
DOI: 10.1111/eea.12517
|View full text |Cite
|
Sign up to set email alerts
|

Influence of no‐tillage practices and later planting date on the pea leaf weevil, Sitona lineatus, in pea, Pisum sativum

Abstract: The pea leaf weevil, Sitona lineatus (L.) (Coleoptera: Curculionidae), is a periodic pest of pea, Pisum sativum L. (Fabaceae), in the Palouse region of northern Idaho and eastern Washington, USA. Previous work on‐station and in commercial pea fields showed initial adult weevil colonization was greater in conventional‐tillage than in no‐tillage fields. Increased surface residue of no‐tillage systems results in cooler soils with greater available moisture typically resulting in later planting dates for conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In this context, the sowing date also plays a role. If the pea leaves are available earlier, colonisation by pea weevils begins earlier [ 63 ]. The authors also demonstrated that cereal residues of the previous year’s crop inhibited the ability of the beetles to locate the host plants.…”
Section: Integrated Pest Managementmentioning
confidence: 99%
“…In this context, the sowing date also plays a role. If the pea leaves are available earlier, colonisation by pea weevils begins earlier [ 63 ]. The authors also demonstrated that cereal residues of the previous year’s crop inhibited the ability of the beetles to locate the host plants.…”
Section: Integrated Pest Managementmentioning
confidence: 99%
“…Joseph () is studying the effects of planting date, temperature, and moisture on feeding injury by the collembolan Protaphorura fimata (Gisin) (Collembola: Onychiuridae), a serious pest of lettuce in coastal California, USA. Studies by Hanavan & Bosque‐Pérez () with pea weevil, Sitona lineatus (L.) (Coleoptera: Curculionidae), in conventional and no‐till peas suggest that lower weevil abundance in no‐till treatments is due to reduced plant apparency and crop availability during the peak colonization period.…”
mentioning
confidence: 99%